The Fund and Non-Member States Some Legal Effects. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1966)
This paper examines legal provisions and practices of the IMF that involve nonmember states. It considers certain preliminary topics including: categories of nonmembers, subordinate territories for which members are responsible, and ex-members. It then discusses three ways in which nonmembers are affected either because members are limited in their freedom of action in dealing with nonmembers or because nonmembers have consented to certain obligations or standards that parallel those of the Articles. Withholding of certain benefits from nonmembers is also outlined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet